Nitrosative events in atopic asthma pathogenesis - Parilova, O.O.; Volodina, T.T.; Shandrenko, S.G. (Вiopolymers and Cell, 2015)
The correlation between high exhaled nitric oxide levels and eosinophilic-mediated airway inflammation in patients with atopic asthma has been well documented. This generates prerequisites that a regulatory feedback mechanism exists between them. Therefore, the paper briefly describes evidence implementing biosynthesis, enzyme structural features, expression regulation of its isoforms and effects of nitric oxide, which have helped elucidate molecular mechanisms by which nitric oxide selectively promotes asthma exacerbation. In previous study we have demonstrated that airway infiltrate of immune cells contributes to NO synthesis in the respiratory tract during allergic inflammation under guinea pig model of acute asthma with multiple challenges. On the basis of these findings the authors posits that nitric oxide represents an additional signal of the induction of Th2 subset response and be considerably involved in the complex network of immune regulation distinctive for atopic asthma phenotype.